2015
DOI: 10.1002/chem.201405733
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Transition‐Metal‐Ion Stress Induces Prodigiosin Biosynthesis in Streptomyces coelicolor M145: Formation of Coeligiosins

Abstract: The bacterium Streptomyces coelicolor M145 reacts to transition-metal-ion stress with myriad growth responses, leading to different phenotypes. In particular, in the presence of Co 2 + ions (0.7 mm) S. coelicolor consistently produced a red phenotype. This phenotype, when compared to the wild type, differed strongly in its production of volatile compounds as well as high molecular weight secondary metabolites. LC-MS analysis revealed that in the red phenotype the production of the prodigiosins, undecylprodigio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In line with several previous studies, these groups of chemicals were also reported in the bacterial fermentation broth or extracts derived from Actinomycetes and Streptomyces sp. For instance, dimethyltrisulfide ( 1 ) (Groenhagen, Maczka, Dickschat, & Schulz, ), trimethylpyrazine ( 2 ) (Citron, Barra, Wink, & Dickschat, ), 2‐acetylpyrrole ( 3 ) (Morgenstern, Paetz, Behrend, & Spiteller, ), pyrazine,2,5‐dimethyl‐3‐(3‐methylbutyl) ( 4 ) (Citron et al, ), phenol,2,4‐bis(1,1‐dimethylethyl)‐ ( 8 ) (Kumar, Duraipandiyan, & Ignacimuthu, ), benzoic acid,4‐ethoxy‐,ethyl ester ( 9 ) (Sharma, Goel, Dureja, & Uniyal, ), (3R,8aS)‐3‐methyl‐1,2,3,4,6,7,8,8a‐octahydropyrrolo[1,2a]pyrazine‐1,4‐dione ( 13 ) (Tan et al, ), pyrrolo[1,2a]pyrazine‐1,4‐dione, hexahydro ( 14 ) (Ser, Palanisamy, et al, ), 1,4‐diaza‐2,5‐dioxo‐3‐isobutyl bicyclo[4.3.0]nonane ( 15 ) (Ser, Ab Mutalib, et al, ), 9H‐Pyrido[3,4‐b]indole ( 16 ) (Tan, Ser, et al, ), 2,5‐piperazinedione, 3‐(1‐methylethyl)‐6‐(phenylmethyl)‐ ( 17 ) (Alshaibani et al, ), 3‐benzyl‐1,4‐diaza‐2,5‐dioxobicyclo[4.3.0]nonane ( 18 ) (Jog, Pandya, Nareshkumar, & Rajkumar, ; Sharma, Kalita, & Thakur, ) and phenol,2,2′‐methylenebis[6‐(1,1‐dimethylethyl)‐4‐methyl‐ ( 19 ) (Tan, Ser, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with several previous studies, these groups of chemicals were also reported in the bacterial fermentation broth or extracts derived from Actinomycetes and Streptomyces sp. For instance, dimethyltrisulfide ( 1 ) (Groenhagen, Maczka, Dickschat, & Schulz, ), trimethylpyrazine ( 2 ) (Citron, Barra, Wink, & Dickschat, ), 2‐acetylpyrrole ( 3 ) (Morgenstern, Paetz, Behrend, & Spiteller, ), pyrazine,2,5‐dimethyl‐3‐(3‐methylbutyl) ( 4 ) (Citron et al, ), phenol,2,4‐bis(1,1‐dimethylethyl)‐ ( 8 ) (Kumar, Duraipandiyan, & Ignacimuthu, ), benzoic acid,4‐ethoxy‐,ethyl ester ( 9 ) (Sharma, Goel, Dureja, & Uniyal, ), (3R,8aS)‐3‐methyl‐1,2,3,4,6,7,8,8a‐octahydropyrrolo[1,2a]pyrazine‐1,4‐dione ( 13 ) (Tan et al, ), pyrrolo[1,2a]pyrazine‐1,4‐dione, hexahydro ( 14 ) (Ser, Palanisamy, et al, ), 1,4‐diaza‐2,5‐dioxo‐3‐isobutyl bicyclo[4.3.0]nonane ( 15 ) (Ser, Ab Mutalib, et al, ), 9H‐Pyrido[3,4‐b]indole ( 16 ) (Tan, Ser, et al, ), 2,5‐piperazinedione, 3‐(1‐methylethyl)‐6‐(phenylmethyl)‐ ( 17 ) (Alshaibani et al, ), 3‐benzyl‐1,4‐diaza‐2,5‐dioxobicyclo[4.3.0]nonane ( 18 ) (Jog, Pandya, Nareshkumar, & Rajkumar, ; Sharma, Kalita, & Thakur, ) and phenol,2,2′‐methylenebis[6‐(1,1‐dimethylethyl)‐4‐methyl‐ ( 19 ) (Tan, Ser, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This production of secondary metabolites is attributed to the development of aerial hyphae as a result of nutrient limitation [47]. The biological activity of these compounds involves inhibitory or microbiocide activity against microorganisms (i.e., antibiotics), toxicity against metazoans, microbial hormonelike activity, and metal transport [48][49][50]. It has been well demonstrated that the secondary metabolites produced by streptomycetes increases adaptation to biological, physical, and chemical stresses; thus, they are recognized as 'stress metabolites' [36].…”
Section: Morphological Differentiation and Physiologymentioning
confidence: 99%
“…Time-space monitoring of redD expression, the activator of PdGs red biosynthetic genes, is also confined to aging, lysed filaments ( Sun et al, 1999 ). Moreover, prodigiosin-like pigments are induced by stressing culture conditions like excess of metal ions and pH shock ( Mo et al, 2013 ; Morgenstern et al, 2015 ), co-cultivation with competing microorganisms ( Luti and Mavituna, 2011b ; Schäberle et al, 2014 ), and feeding the medium with dead bacterial cells ( Luti and Mavituna, 2011a ). Finally, all other DNA-damaging agents have been shown to be toxic for the producing actinobacterial species ( Tenconi and Rigali, 2018 ).…”
Section: Introductionmentioning
confidence: 99%